Soil quality indicators to assess functionality of restored soils in degraded semiarid ecosystems - Muñoz-Rojas, Miriam; Erickson, T.; Dixon, Kingsley; Merritt, D. (Blackwell Science Inc., 2016)
© 2016 Society for Ecological Restoration. A thorough knowledge of soil functionality is critical to successful restoration of disturbed ecosystems, and its evaluation involves the assessment of soil properties and processes as a component of a healthy ecosystem. Here, we propose a set of soil quality indicators to assess the soil status in restored soils (topsoil and waste material) and test new methods that are easy to apply, interpret, and cost-effective for the analysis of soil biological indicators in restored ecosystems. We show that in addition to organic carbon and C:N ratio, biological indicators (microbial diversity and activity in particular) are the most sensitive indicators to detect differences among reconstructed soils and analogue undisturbed soils in semiarid areas. The use of the 1-day CO2 test is proven to be an alternative cost- and time-effective method to measure microbial activity and assess soil functionality of restored soils. Our results show a positive effect of vegetation on reconstructed soils and a recovery of soil functionality in waste material to levels similar to topsoil once vegetation is established. However, soil functionality in both restored waste materials and topsoils is still far from that in undisturbed native soils. We conclude that soil functionality is critical in the restoration process, particularly in semiarid areas, and the methods used here could be effectively applied in a broad range of restoration projects in arid and semiarid environments.